Family communication about genomic sequencing: A qualitative study with cancer patients and relatives. Issue 5 (May 2021) - Smit, Amelia K; Bartley, Nicci; Best, Megan C; Napier, Christine E; Butow, Phyllis; Newson, Ainsley J; Tucker, Kathy; Ballinger, Mandy L; Thomas, David M; Jacobs, Chris; Meiser, Bettina; Goldstein, David; et al.
Highlights: Clinical genomic sequencing warrants the investigation and potential development of family-centered communication interventions. Preference-sensitive family communication strategies about genomic testing are needed. Support needs should be assessed specific to clinical applications of genomic testing. Abstract: Objective: This study explored family communication about undertaking genomic sequencing, and intentions to communicate pertinent heritable results to family members. Methods: Semi-structured interviews were conducted with cancer patients (n = 53) and their relatives (n = 20) who underwent germline genome sequencing or molecular tumor testing. Interviews were audio-recorded, transcribed and analyzed using thematic analysis. Results: Key themes relevant to family communication about undertaking sequencing included: perceiving family member interest, delaying discussion until results were received, having shared capacity to understand and cope, and having open communication in the family. Intended communication subsequent to receiving results was affected by: disease severity, risk management options, degree of closeness in the family, sense of responsibility, and potential adverse impacts on family. Resource and support needs varied based on the complexity of test results, health professionals' availability, and disease severity. Unique subthemes were identified for specific subgroups. Conclusion: Current findings support the need to assess the impact and resource needs specific to each clinical application of genomic sequencing. Practice implications: Increasingly sophisticated and complex clinical genomic sequencing warrants development of family-centered interventions and resources to facilitate preference-sensitive communication about genomic sequencing, including disseminating relevant information to family members.